Gestão patrimonial: contribuição para o controle de bens móveis na Universidade Federal do Rio Grande do Norte - Matias, Anderson Cortez (2015)
The Asset Management is in accordance with action to ensure, through records and documentation, collection of data relating to identity, existence, amount, location, conditions of use and history of assets since its inclusion in equity until its low end, whatever the reason. It can be seen in the current equity legislation certain lack with regard to the detailed procedures of asset management, namely: receiving, tipping, registration, inventory, preservation and undoing goods. These loopholes in the law deserve the search for alternatives to improve the effective control and performance of activities in asset management, as the quantity and value of goods are increasingly representative within public institutions. The aim of this study was to contribute to the improvement of Asset Management at the Universidade Federal do Rio Grande do Norte (UFRN). The research is characterized as having descriptive and exploratory design and qualitative analysis research. In the data collection process was used participant observation in the Diretoria de Material e Patrimônio and document analysis reports issued by the Sistema Integrado de Patrimônio, Administração e Contratos (SIPAC-UFRN). From the collection phase until the undo phase of the well it was revealed several nonconformities present in the routine of the heritage sector, such as lack of physical space for receiving and storage of goods, lack an awareness policy for the reuse of goods collected in condition of use, the inventory is not being done systematically, among others. Therefore, they did suggest some solutions to improve the effective control and process performance in asset management and propose an inventory process model appropriate to the reality of UFRN. It was concluded from this study that the management process of movable property in UFRN is intended only to meet the legal requirements and to improve asset management is necessary to discipline and standardize procedures through well-defined processes to have an efficient and effective control in order to reduce costs and increase the transparency of the control of goods.